Implementing sustainability frameworks at a product-level – Exploring the usability - Paule Bhérer-Breton; Anna Woodhouse; Bente Aspeholen Åby; Hilke Bos-Brouwers; Melanie Kok; Hanne Fjerdingby Olsen (Environmental and Sustainability Indicators)
Product-level assessments are for targeted and effective sustainability improvements both in downstream and upstream agrifood supply chains. Current frameworks for sustainability assessments often lack the integration of both social and environmental considerations for product-specific assessment. This study explores the usability of existing frameworks designed for both social and environmental assessments, with a focus on their application at the product level. Based on the development of usability criteria and applying a waterfall selection process, we identified two frameworks (Food System Sustainable framework and Sustainable Nutrition Security framework) for further analysis. To test against usability, both frameworks were applied towards a case study of seven food products produced in Norway: milk, greenhouse tomatoes, greenhouse cucumbers, wheat, beef, sheep and pork. The criteria included the following: data availability, data correctness, ease of use, transparency, effectiveness or relevance, and complexity of use. The selected frameworks provided a holistic and comprehensive approach to assessing social and environmental sustainability. However, their usability was limited due to lower data accuracy and a lack of user-friendliness for researchers, who were the primary target user group. The study revealed a trade-off: frameworks with higher usability tended to sacrifice depth and comprehensiveness in the information provided about food products. Both frameworks faced significant challenges in distinguishing social and ethical issues at the product level, largely due to data limitations. These findings underscore the need for the development of a purpose-built framework that accounts for these trade-offs, while enhancing usability, is essential to progress toward a more sustainable food supply chain.